Design of reconfigurable mechanism for underactuated robot in the grounded applications. Issue 1 (31st December 2022) - Ngo, Ha Quang Thinh; Cao Tri, Huynh; Tu, Nguyen Thanh; Bao, Danh Nguyen the; Anh Duy, Phan Lu; Phat, Khuu Minh; Duy, Tran Anh; Tin, Ngo Truong
Abstract: In the robotic applications, wheel-legged robot provides many advantages such as lightweight, superior performance, low energy consumption and wide development prospects. Especially, in some emergent cases, it has the ability to move flexibly, pass obstacles and work in both outdoor and indoor environment. In this paper, a novel design of wheel-legged platform for robotic investigation is presented. Firstly, the principle diagram of underactuated robot (UR) is outlined owing to the model of inverted pendulum. Then, several theoretical computations are suggested to ensure the ability to work as its desired control. Later, an overview of mechanical design in 3D is described as well as the design of electrical circuit is demonstrated based on these requirements. To validate the feasibility and effectiveness of our approach, several numerical simulations are carried out.